1999
DOI: 10.1038/sj.cgt.7700085
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated endocytosis of G250 tumor-associated antigen allows targeted gene transfer to human renal cell carcinoma in vitro

Abstract: Specific gene transfer into targeted tumor cells remains a critical issue for the development of systemic gene therapy protocols. With this end in view, we have tested the possibility of selectively directing genes to tumor cells through the recognition of tumor-associated antigens (TAA). This was approached in vitro on four human renal cell carcinoma (RCC) lines by means of the highly specific mouse G250 monoclonal antibody (mAb) chemically conjugated to a plasmid DNA conveying a reporter activity. This mAb d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(36 reference statements)
3
16
0
5
Order By: Relevance
“…Human renal carcinoma cell lines (RCC, kindly obtained from E Angevin, IGR, France, were maintained in culture as described (Durrbach et al, 1999). The presence of EPO receptors was determined by cytofluorometry using a specific mouse antihuman EPO receptor mAb IgG2b (R&D Systems) or a control isotypic IgG2b mAb (Caltag Laboratories), both revealed with an FITC-labeled goat anti-mouse IgG2b (Jackson Immuno Research Laboratories).…”
Section: Cell and Culture Conditionsmentioning
confidence: 99%
“…Human renal carcinoma cell lines (RCC, kindly obtained from E Angevin, IGR, France, were maintained in culture as described (Durrbach et al, 1999). The presence of EPO receptors was determined by cytofluorometry using a specific mouse antihuman EPO receptor mAb IgG2b (R&D Systems) or a control isotypic IgG2b mAb (Caltag Laboratories), both revealed with an FITC-labeled goat anti-mouse IgG2b (Jackson Immuno Research Laboratories).…”
Section: Cell and Culture Conditionsmentioning
confidence: 99%
“…Besides application of chemokines, application of antibodies, particularly anti-G250, 30 which is expressed by >95% of RCCs, 31 should be mentioned. The antibody becomes internalized, 32 and application of 125 I-coupled G250 has been reported to retard tumor progression. [33][34][35] Cell-mediated immunotherapeutic protocols in RCC have been based on tumor lysate-loaded DCs.…”
mentioning
confidence: 99%
“…Antibody's facilitating effects on gene transfer have also been observed for conventional gene transfer systems using particulate complexes of an antibody and DNA [19][20][21] or those further combined with viruses [22], cationic polymers [23], lipids [24] and/or calcium phosphates [25]. For example, Kozlova et al showed that the covalent attachment of a CD11c antibody onto calcium phosphate-based nanoparticles increased gene transfer efficiency for the CD11c-positive cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the immobilized antibody in gene transfer has not yet been fully clarified, but we believe that antigen-antibody binding at the cell-layer interface could be responsible for the increased gene transfer capability of the DA-Ap layer compared with that of the D-Ap layer. Antigen-antibody binding can facilitate gene transfer by enhancing the adhesion of cells to the DA-Ap layer and/or by promoting endocytosis by the cell [20,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation